From Barriers to Breakthroughs: A Deep Dive into BIM Integration Challenges - Terfa Caleb Agwa; Tahir Celik (Buildings)
Building Information Modeling (BIM) has significantly impacted the global construction industry, promising efficiency, cost savings, and improved project outcomes. However, its adoption in developing countries, such as Nigeria, remains inconsistent due to multiple barriers. This study aims to investigate the barriers hindering the adoption of BIM in Nigeria’s construction sector, with a view to providing strategic recommendations for stakeholders. A mixed-methods approach was employed, combining a comprehensive literature review with semi-structured interviews from 10 experts in Nigeria, representing both industry and academia. A hybrid analytical methodology, integrating the Analytical Hierarchy Process (AHP) and fuzzy Technique for Order Preference by Similarity to the Ideal Solution (TOPSIS), was used to analyze the data, because they provide a comprehensive framework for informed decision-making. Technical barriers are identified as the most significant challenge to BIM adoption, particularly due to difficulties in accessing advanced technology. Educational barriers also play a major role, with limited awareness among industry professionals hindering widespread implementation. Economic constraints further contribute to the slow adoption, as financial limitations impact investment in necessary tools and training. The study provides policy implications and recommendations, including the development of a national BIM evaluation framework, improved training programs, and government support for standardization. These recommendations are expected to facilitate informed decision-making among stakeholders and promote effective BIM adoption in Nigeria’s construction industry, serving as a roadmap for other developing countries facing similar challenges.